ABILITY OF AMILOLYTIC BACTERIA (Bacillus paramycoides AND Enterobacter cloacae) IN DEGRADING ORGANIC MATERIALS OF MANGROVE LITTLE - Putri, Redila Aprilivia; Nursyirwani, Nursyirwani; Feliatra, Feliatra (Asian Journal of Aquatic Sciences, 2021)
This study aims to find out that Bacillus paramycoides and Enterobacter cloacae bacteria can produce amylase enzymes and have the ability to degrade organic matter, especially mangrove litter. From this study it was found that the optimal growth of B.paramycoides and E. cloacae bacteria occurred at 12th hour. The results of measurements and calculations of absorbance values ​​at 630 10.238 x 108 cells/mL (B. paramycoides) and 12.030 x 108 cells/mL (E. cloacae) using the spectrophotometric method. Meanwhile, with the TPC method at 12 hours, the number of bacterial cells was 2.08 x 108 CFU's/mL (B.paramycoides) and 2.44 x 108 CFU's/mL (E. cloacae). The ability to produce the largest amylolytic bacterial amylase enzyme also occurred at 12 hours as much as 0.306 mg/mL (B.paramycoides) with an increase of 0.046 mg/mL and 0.243 mg/mL (E. cloacae) with an increase of 0.028 mg/mL. The bacteria that have the highest amylase enzyme ability is E.cloacae as evidenced by the diameter of the clear zone of 10.10 mm. Testing the ability of amylolytic bacteria in degrading mangrove litter was carried out by adding amylase enzyme as much as 0%, 50% and 100%. Amylolytic bacteria can degrade organic matter by hydrolyzing starch contained in mangrove litter. The most degraded starch content was in the 100% enzyme treatment, which was 1.021 mg/mL (B. paramycoides) and 1.189 mg/mL (E.cloacae).